Preferential usage of rifaximin for the treatment of hydrogen-positive small intestinal bacterial overgrowth - Barkin, Jodie A; Keihanian, Tara; Barkin, Jamie S; Antequera, Carol M; Moshiree, Baharak (Revista de Gastroenterología del Perú, 2019)
Objectives: Small intestinal bacterial overgrowth (SIBO) is challenging to treat and diagnose and is associated with diagnosis of irritable bowel syndrome (IBS). Although no FDA-approved medications exist for treatment of SIBO, rifaximin has recently received approval to treat diarrhea-predominant IBS and patients with methane-positive SIBO breath tests. The aim of this study is to evaluate patient response to rifaximin for SIBO based on breath test results. Materials and methods: All patients underwent breath testing to evaluate for SIBO during a 42-month period. Patients were defined as having a positive glucose breath test for SIBO based on an increase of ≥ 20 ppm of hydrogen and/or ≥ 10 ppm of methane 90 minutes after ingesting glucose. Patient demographic and symptom data, antibiotic treatment regimens, symptomatic response to therapy, and repeat treatments were recorded. Institutional review board approval was obtained. Results: A total of 53 of 443 patients had positive breath testing for SIBO. Response rates to rifaximin (550 mg three times daily for 14 days) were 47.4% for hydrogen positivity alone and 80% for both hydrogen and methane positivity. Conclusions: Rifaximin was the most commonly prescribed antibiotic regimen for SIBO therapy. Patients with hydrogen or hydrogen and methane positive breath tests responded well to rifaximin therapy. For patients with hydrogen-positive SIBO, rifaximin may prove a highly effective therapy in providing symptom relief from the effects of SIBO.